The Influence of Hedonic Motivation, Store Atmosphere and Positive Emotion on Consumer Impulse Buying - Hasanudin Alfahri; Endang Silaningsih; Yulianingsih (MultiTech Publisher, 2025)
This study aims to determine the effect of hedonic motivation, store atmosphere and positive emotion on consumer impulse buying. This study is a quantitative study with a survey method. The population in this study were consumers of the Nako Kuntum coffee cafe who had made at least one purchase. The results of this study indicate that: (1) Hedonic Motivation does not have a positive effect on impulse buying. (2) Store atmosphere does not have a positive effect on impulse buying. (3) Positive emotion has a positive effect on impulse buying.